Impact of micro campaigns of ROBI on customer life- cycle management at telecommunication industry - Jinia, Sumona Parvin (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2018.